Learning diaries in startup education : an empirical & comparative study - Lahti, Sonja (2020)
The concept of startups and startup education has been recently rising in higher education. The concepts of entrepreneurship education, innovativeness, and challenge-based learning are themes that have been taught similarly to startup education. The startup education is a relatively new topic and the ways of doing startup education have been relatively little studied. This thesis aims to understand how learning diaries can be effectively used in startup education and how the learning diaries can be beneficial.